Interaksi Sosial Muslim-Kristiani di Sumatera Utara (Studi tentang Hubungan Keduanya di Pemukiman) - Irwansyah Irwansyah (TSAQAFAH, 2014)
The problem of this research is the social interaction that occurs between Muslims and Christians in the little settlements of North Sumatra. This study is a field study conducted with the sociological approach to religion. The capture of data is through interviews and field observations after firstly identifying the areas of Muslims and Christians in North Sumatra. The data analysis was performed by borrowing Kahane’s opinion, an American sociologist who researched in Indo- nesia and revealed that the social condition of Indonesian people which is “diffuse but not perfect” potentially result in conflict, especially conflict based on primordial disintegration factors, such as poor relationship between Islam and non-Islam. By borrowing the analysis model of Kahane in sociological view, the author analyzed Muslim-Christian relationship in North Sumatra allows such relationships positively or negatively, and then analyzed the causal factors of these relationships. The results showed the social interaction that occurs between Muslims and Christians in North Sumatra formed in different patterns depending on the model and residential areas. In the model of blend settlements, social interaction tend to be positive, but in clustered settlements, the models of social interaction tends to be negative. In addition, the church built by Christians in predominantly Muslim neighborhoods also tend to lead to conflict, and this conflict usually driven by outsiders’ provocative statement. Additionally, the pig farm is also a crush barrier that destabilizes social interaction between Muslim and Christian in these settlements.